The designated mourner [videorecording (DVD)] - Hare, David, 1947-; Hare, David, 1947-; Shawn, Wallace; Nichols, Mike; Richardson, Miranda; De Keyser, David; Shawn, Wallace (First Look Home Entertainment, 1999)
Set in an unnamed repressive country, possibly in the near future, a married couple and the wife's father discuss, directly with the audience, their lives and the death of culture.